2018
DOI: 10.2147/cmar.s159563
|View full text |Cite
|
Sign up to set email alerts
|

An expression signature model to predict lung adenocarcinoma-specific survival

Abstract: BackgroundThe current TNM staging system plays a central role in lung adenocarcinoma (LUAD) prognosis. However, it may not adequately stratify the risk of tumor recurrence. With the aid of gene expression profiling, we identified 31 lncRNAs whose expressions in tumor tissues could be used as a risk indicator for the guidance of lung cancer therapy. This exploratory analysis may shed new light on identification of potential prognostic factors.Materials and methodsA survival prediction scoring model was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
2
34
1
Order By: Relevance
“…Study has shown that the great expression level of RP11-108K3.2 correlated with low overall survival of CRC, and this result was consistent with our study [15]. In a study on lung adenocarcinoma, the researchers study 346 differentially expressed lncRNAs, of which RP11-108K3.2 is highly expressed in lung cancer tissues [16]. ACADL GFRA3 CLVS2 ALPI CCNO NGB RASSF8 RBPMS2 PNPLA3 ACSBG1 FOLR2 RASSF10 MB MCIDAS AP1S2 GRB7 RBPMS LIPG FERMT1 FERMT2 SLC26A2 SLC13A2 KIF5C LMO3 HAND2 FAM13C CPXM2 TUBB2B CSRP1 PHOX2B FIGF CLU LYVE1 PRRT2 C7 COL6A2 LEPREL1 COL21A1 COL9A1 COL10A1 CRTAP CHL1 COLGALT2 PRKAA2 FABP4 ITGA7 MYOT LEPR EBF1 FABP6 TMTC1 IL32 ACKR1 METTL7A CHI3L1 HBB CXCL1 CCL2 HBG1 ITGA2 ITGA5 PTGER3 ADIPOQ SLC2A4 LCN2 FLNC ADAMTS14 THSD7A COL11A1 PCOLCE2 TMEM179 CKS2 E2F7 KIF24 RECQL4 REEP2 CA9 SMPX IP6K3 KCNIP3 ASB5 ZBTB16 FBXO41 HJURP Figure 3: The protein-protein interaction network of differentially expressed mRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…Study has shown that the great expression level of RP11-108K3.2 correlated with low overall survival of CRC, and this result was consistent with our study [15]. In a study on lung adenocarcinoma, the researchers study 346 differentially expressed lncRNAs, of which RP11-108K3.2 is highly expressed in lung cancer tissues [16]. ACADL GFRA3 CLVS2 ALPI CCNO NGB RASSF8 RBPMS2 PNPLA3 ACSBG1 FOLR2 RASSF10 MB MCIDAS AP1S2 GRB7 RBPMS LIPG FERMT1 FERMT2 SLC26A2 SLC13A2 KIF5C LMO3 HAND2 FAM13C CPXM2 TUBB2B CSRP1 PHOX2B FIGF CLU LYVE1 PRRT2 C7 COL6A2 LEPREL1 COL21A1 COL9A1 COL10A1 CRTAP CHL1 COLGALT2 PRKAA2 FABP4 ITGA7 MYOT LEPR EBF1 FABP6 TMTC1 IL32 ACKR1 METTL7A CHI3L1 HBB CXCL1 CCL2 HBG1 ITGA2 ITGA5 PTGER3 ADIPOQ SLC2A4 LCN2 FLNC ADAMTS14 THSD7A COL11A1 PCOLCE2 TMEM179 CKS2 E2F7 KIF24 RECQL4 REEP2 CA9 SMPX IP6K3 KCNIP3 ASB5 ZBTB16 FBXO41 HJURP Figure 3: The protein-protein interaction network of differentially expressed mRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, previous studies have shown that RP11-108K3.1 could serve as a potential independent biomarker for the prognostic prediction of colorectal cancer [18] . RP11-108K3.1 is one of the DElncRNAs in lung adenocarcinoma [19] . However, no study so far has reported any association of RP11-109M17.2 with cancer, which means that it may serve as a novel therapeutic target in TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…These long molecules are dysregulated among cancers (Yan et al, 2015) and play key roles in gene regulation and carcinogenesis, including proliferation, survival, migration, and genomic stability (Gutschner et al, 2013;Castro-Oropeza et al, 2018). It is believed that the clinical value of lncRNA is not confined to candidate biomarkers for diagnostic and prognostic purposes (Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%